Discourse prominence effects on 2.5-year-old children's interpretation of pronouns - Song, Hyun-joo; Fisher, Cynthia (Lingua, 2007)
Three experiments examined 2.5-year-olds’ sensitivity to discourse structure in pronoun interpretation. Children heard simple two-character stories illustrated by pictures on two video screens. In Experiments 1 and 2, one character in each story was established as more prominent than the other in several context sentences because it was mentioned first, appeared in subject position, was mentioned more often, and was pronominalized once. In Experiment 3, one character was singled out as more prominent only by being mentioned first and placed in subject position. In all three experiments, after hearing a pronoun subject in the final (test) sentence of each story, children looked longer at the character established as more prominent in the preceding sentences. These experiments show that 2.5-year-olds, like older children and adults, interpret pronouns relative to a discourse representation in which referents are ranked in prominence, and that the prominence of discourse referents is influenced by some of the same factors that guide pronoun interpretation in adulthood.